Effects of Hemantane upon the level of lipid peroxidation in brain in experimental parkinsonian syndrome - E. A. Ivanova; I. G. Kapitsa; N. N. Zolotov; E. A. Valdman; A. V. Nepoklonov; K. N. Kolyasnikova; T. A. Voronina (Фармакокинетика и Фармакодинамика, 2016)
In two animaL modeLs of parkinsonian syndrome - induced by 1-methyL-4-phenyL-1,2,3,6-tetrahydropiridine (MPTP) in C57BL/6 mice and 6-hydroxidopamine (6-OHDA) in rats noveL antiparkinsonian drug hemantane was shown to reduce the increase of brain LeveL of Lipid peroxidation caused by both neurotoxines. In prefrontaL cortex and striatum of mice which were treated with hemantane 10 mg/kg 5 days before MPTP and 5 days together with MPTP and in rats which received hemantane during 21 days after 6-OHDA injection in mediaL forebrain bundLe the LeveLs of maLondiaLdehyde and conjugated dienes were significantLy Lower than in untreated animaLs. The data obtained is consistent with antioxidant properties of hemantane.